The effect of terminal impedance on aortic morphology and hemodynamics: an in vitro phantom study using flow field visualization - Chen, Huimin; Wang, Wenjun; Liu, Dengji; Cao, Zhen; Yang, Yi; He, Ying; Chi, Qingzhuo (Frontiers in Bioengineering and Biotechnology, 2023)
To investigate the risk factors for aortic dissection tearing, we fabricated a simplified patient-specific aortic silicone phantom using the brush-spin-coating method. The aortic phantom only includes the aorta from the ascending aorta to the descending aorta, without other branches. We designed two experiments to investigate the alteration of aortic morphology and intravascular hemodynamics using the particle image velocimetry method. The results revealed dilation and elongation of the aortic phantom, especially the ascending aorta, after the phantom’s terminal resistance was increased. Additionally, the particle image velocimetry results demonstrated an increased vortex region, which caused the inner side of the aortic wall to become scoured by blood. This study suggests that the deformation of the inner side aortic wall and the change in hemodynamics in response to the increased terminal resistance may be a risk factor for aortic tearing and should be monitored.